A computational study on magnetic effects of Zn 1 -xCrxO type diluted magnetic semiconductor - DEĞER, CANER (Elsevier B.V., 2015)
Diluted magnetic semiconductors (DMS) have been intensely investigated both experimentally and theoretically in recent years. In spite of large body of studies to have a better understanding on working principles of devices based on DMS materials and taking a detailed control during fabrication process, nature of the system remains largely unknown. It is proposed that dominant contribution to DMS Hamiltonian is originated from ferromagnetic interaction between antiferromagnetic Cr+3 and its nearest neighbors rather than long-range interactions which commonly reported. In the light of experimental data obtained from literature, we simulated Zn1-xCrxO wurtzite thin film based on Metropolis algorithm and Markov Chain Monte Carlo (MC-MC) method as realistic as possible. We found that the soft ferromagnetic behaviour of Zn1-xCrxO thin film emerges by increasing doping ratios up to 15% (x=0.15), then it gradually vanishes above 15% (x=0.15) at room temperature. Results obtained here was found to be highly consistent with experimental studies. © 2015 Elsevier B.V. All rights reserved.
Keywords: Diluted magnetic semiconductors; Exchange-bias; Monte Carlo simulation; Soft ferromagnetism